Environmental Innovations as a Factor of Increasing the Economic Efficiency of Production. Study Case: Pavlodar Region - ARYNOVA, Zylfiya Amangeldinovna; KAIDAROVA, Lyazzatkenovna; SARTOVA, Rysty Bozmanaevna; BAYANDINA, Gulmira Duisenbaevna; RAKHMETULLINA, Shynar Zhakanovna; ZHETESSOVA, Mariyam Turashevna (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
The relevance of the research topic is that the world has turned its face to the environmental problem, which is the created real threat of a global environmental catastrophe. The aggravation of relations between society and the environment is facilitated by a technogenic type of economic development, of a nature-destructive nature, based on the use of natural resources and means of production without taking into account environmental restrictions. Environmental innovations as a factor in increasing the economic efficiency of production in order to improve products and services require the development of technologies, which include environmentally friendly biotechnology, waste processing technologies, low-polluting technologies, etc. There is a need for radical changes in the methods and means of environmental protection, which reduce the technogenic impact on the biosphere of the Earth, and contribute to the preservation of human health.